The New Street Gasworks, Caltongate: archaeological investigation of a major power production complex in the heart of Edinburgh and its significance in the industrial development of Britain (Scottish Historical and Archaeological Internet Reports, 2022)
An extensive programme of archaeological fieldwork between August 2006 and May 2008 in the area of the former New Street Gasworks and New Street Bus Depot, Canongate, Edinburgh revealed remains of one of the earliest and most significant gasworks in Britain. As well as patches of medieval and post-medieval backland soils and post-medieval structures that pre-dated the establishment of the New Street works in the first quarter of the 19th century, substantial structural remains of the various phases of this industrial undertaking were recorded, along with a suite of associated artefacts.These works have permitted the exploration of the industrial heritage of Edinburgh, as well as revealing important evidence of the medieval and post-medieval occupation of the Canongate. This is the first major excavation of an urban gasworks in Scotland and has enabled an examination of how these gasworks functioned and how they expanded with the introduction of more efficient systems and new technology.